The customer-driven playbook : converting customer feedback into successful products - Lowdermilk, Travis; Rich, Jessica (O'Reilly Media, Inc., 2017)
"Despite the wide acceptance of Lean approaches and customer-development strategies, many product teams still have difficulty putting these principles into meaningful action. That's where The Customer-Driven Playbook comes in. This practical guide provides a complete end-to-end process that will help you understand customers, identify their problems, conceptualize new ideas, and create fantastic products they'll love. To build successful products, you need to continually test your assumptions about your customers and the products you build. This book shows team leads, researchers, designers, and managers how to use the Hypothesis Progression Framework (HPF) to formulate, experiment with, and make sense of critical customer and product assumptions at every stage. With helpful tips, real-world examples, and complete guides, you'll quickly learn how to turn Lean theory into action. Collect and formulate your assumptions into hypotheses that can be tested to unlock meaningful insights ; Conduct experiments to create a continual cadence of learning ; Derive patterns and meaning from the feedback you've collected from customers ; Improve your confidence when making strategic business and product decisions ; Track the progression of your assumptions, hypotheses, early ideas, concepts, and product features with step-by-step playbooks ; Improve customer satisfaction by creating a consistent feedback loop"--Provided by publisher.